2020
DOI: 10.3847/1538-3881/ab5afa
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Characterization and Further Orbital Modeling of κ Andromeda b

Abstract: We present κ Andromeda b's photometry and astrometry taken with Subaru/SCExAO+HiCIAO and Keck/NIRC2, combined with recently published SCExAO/CHARIS low-resolution spectroscopy and published thermal infrared photometry to further constrain the companion's atmospheric properties and orbit. κ And b's Y/Y-K colors are redder than field dwarfs, consistent with its youth and lower gravity. Empirical comparisons of its Y-band photometry and CHARIS spectrum to a large spectral library of isolated field dwarfs reaffirm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 101 publications
(163 reference statements)
2
17
0
Order By: Relevance
“…Since 2013, the high-contrast imagers and spectrographs such as GPI (Macintosh et al 2006), SPHERE (Beuzit et al 2019) or SCExAO/CHARIS (Groff et al 2015;Jovanovic et al 2015) have gathered low-resolution (R λ = 30-350) near-infrared (0.95-2.45 µm) spectra of exoplanets down to 100 mas from their host star. The spectra confirmed some of the results inferred earlier from photometric spectral energy distributions (e.g., Marois et al 2008;Bonnefoy et al 2013): the reduced surface gravity affects the vertical mixing and the gravitational settling of condensates, which leads to thicker cloud layers, upper atmosphere submicron hazes, and causes cloud opacities to remain down to T eff = 600 K at early ages (Bonnefoy et al 2016;Rajan et al 2017;Chauvin et al 2017Chauvin et al , 2018Samland et al 2017;Greenbaum et al 2018;Uyama et al 2020;Delorme et al 2017;Mesa et al 2020). These spectra, however had led to contradicting conclusions on the derivation of the atmospheric composition (Samland et al 2017;Rajan et al 2017), possibly owing to the limited resolution of the observations and uncertainties in the atmospheric models.…”
Section: Introductionsupporting
confidence: 82%
“…Since 2013, the high-contrast imagers and spectrographs such as GPI (Macintosh et al 2006), SPHERE (Beuzit et al 2019) or SCExAO/CHARIS (Groff et al 2015;Jovanovic et al 2015) have gathered low-resolution (R λ = 30-350) near-infrared (0.95-2.45 µm) spectra of exoplanets down to 100 mas from their host star. The spectra confirmed some of the results inferred earlier from photometric spectral energy distributions (e.g., Marois et al 2008;Bonnefoy et al 2013): the reduced surface gravity affects the vertical mixing and the gravitational settling of condensates, which leads to thicker cloud layers, upper atmosphere submicron hazes, and causes cloud opacities to remain down to T eff = 600 K at early ages (Bonnefoy et al 2016;Rajan et al 2017;Chauvin et al 2017Chauvin et al , 2018Samland et al 2017;Greenbaum et al 2018;Uyama et al 2020;Delorme et al 2017;Mesa et al 2020). These spectra, however had led to contradicting conclusions on the derivation of the atmospheric composition (Samland et al 2017;Rajan et al 2017), possibly owing to the limited resolution of the observations and uncertainties in the atmospheric models.…”
Section: Introductionsupporting
confidence: 82%
“…A recent analysis of the CHARIS data by Uyama et al (2020) found a slightly lower temperature using models from Allard et al (2012), Chabrier et al (2000, and Witte et al…”
Section: Temperature Gravity and Metallicitymentioning
confidence: 94%
“…In order to do this, we must construct a model grid that spans the expected values of these parameters. In a number of previous works on κ And b, the temperature was estimated to be ∼2000 K and the surface gravity ( g log )<5 (e.g., Hinkley et al 2013;Bonnefoy et al 2014;Todorov et al 2016;Currie et al 2018;Uyama et al 2020). The metallicity has not been constrained, but estimates from the host star suggest values near solar or slightly subsolar (Wu et al 2011;Jones et al 2016).…”
Section: Synthetic Spectramentioning
confidence: 99%
See 1 more Smart Citation
“…The IFS further plays a key role in studying the atmosphere of the planets by providing a spectrum with low spectral resolution (R = λ/δλ ∼ 20 − 75) of each de-tection. At this resolution, broad molecular absorption bands can be identified, and the pseudo-continuum holds information about the pressure-temperature profile and clouds (e.g., De Rosa et al 2016;Bonnefoy et al 2016;Chilcote et al 2017;Rajan et al 2017;Delorme et al 2017;Samland et al 2017;Bonnefoy et al 2018;Greenbaum et al 2018;Müller et al 2018;Chauvin et al 2018;Currie et al 2018;Uyama et al 2020;Stone et al 2020;Ward-Duong et al 2021).…”
Section: Introductionmentioning
confidence: 99%